Development of teenage pregnancy prevention model for learners in schools in North West Province : implications for policy and practice considerations - Masilo, Daniel Tuelo (University of Limpopo, 2018)
Teenage pregnancy is a social problem that affects and destroys the future of teenage girls, especially teenage learners. Its impact is not only felt by the teenage girls, but also by their families, schools, and the country in general. This study sought to develop an educational social group work model on teenage pregnancy for learners in schools in the North West province. To this effect, this study was anchored on five objectives, namely: to establish the extent of teenage pregnancy amongst learners in schools in the North West province; to assess factors that predispose learners to indulge in sexual activities despite the risk of pregnancy and sexually transmitted diseases; to describe the roles of parents in the prevention of teenage pregnancy amongst learners; to identify prevention measures used by the schools to prevent teenage pregnancy; and to develop, implement, and evaluate an educational social group work model on teenage pregnancy for learners. The study adopted a mixed methods approach by combining the qualitative and quantitative paradigms. The population of the study consisted of learners, while school principals, deputy principals, Life Orientation teachers, and parents/guardians were the key informants. The findings of this study confirm that teenage pregnancy is a serious problem that continues to affect schools. All grades from the secondary schools that participated in this study reported cases of learner pregnancies. The grades with high reported cases include Grades 10, 11, and 12, while Grades 8 and 9 appeared to be the least affected. Furthermore, the findings indicate that male learners are most likely to father children with female learners. The development of an educational social group work model on teenage pregnancy for learners was achieved via a literature review and the empirical findings from learners and the key informants. Group work as a method of the social work profession was chosen in this study because it is intensive in nature, and the follow-up sessions provided a platform for the evaluation of social worker interventions and the performance of individual members and the entire group. The developed model was implemented and evaluated. Different topics were discussed during a marathon of eight
Thesis (Ph. D. (Social Work)) -- University of Limpopo, 2018
Keywords: Teenage pregnancy; Pregnancy prevention model; Teenage learners; North West Province; Implications for policy and practice; Teenage pregnancy; Teenage pregnancy - South Africa - Prevention